Measuring the effective diffusion coefficient of dissolved hydrogen in saturated Boom Clay. (October 2015) - Jacops, E.; Wouters, K.; Volckaert, G.; Moors, H.; Maes, N.; Bruggeman, C.; Swennen, R.; Littke, R.
Highlights: Experiments with H2 are often disturbed by micro organisms. A complex sterilisation procedure was developed. Heat sterilisation, gamma irradiation and the use of a microbial inhibitor were combined. 3 reliable H2 diffusion coefficients were obtained. Abstract: Boom Clay is studied as a potential host formation for the disposal of high-and intermediate level long-lived radioactive waste in Belgium. In such a geological repository, generation of gases (mainly H2 from anaerobic corrosion) will be unavoidable. In order to make a good evaluation of the balance between gas generation vs. gas dissipation for a particular waste form and/or disposal concept, good estimates for gas diffusion coefficients of dissolved gases are essential. In order to obtain an accurate diffusion coefficient for dissolved hydrogen in saturated Boom Clay, diffusion experiments were performed with a recently developed through-diffusion set-up for dissolved gases. Due to microbial activity in the test set-up, conversion of hydrogen into methane was observed within several experiments. A complex sterilisation procedure was therefore developed in order to eliminate microbiological disturbances. Only by a combination of heat sterilisation, gamma irradiation and the use of a microbial inhibitor, reliable, reproducible and accurate H2 (g) diffusion coefficients (measured at 21 °C) for samples oriented parallel ( D eff = 7.25 × 10 −10 m 2 /s and D eff = 5.51 × 10 −10 m 2 /s) and perpendicular ( D eff = 2.64 × 10 −10 m 2 /s) to the bedding plane were obtained.